The Case of the United Kingdom: Mapping Localism, Resilience, and Civic Activism in Response to the COVID-19 Pandemic. Issue 1 (1st December 2021) - Bradley, Tony; Malki, Issam; Ziniel, Curtis; Ghalib, Asad
Abstract: This article explores the determinants of local resilience in the form of local COVID-19 mutual aid groups. These groups were formed to offer mutual help to those who had experienced a loss of social quality. We test a series of hypotheses, considering which conditional factors are most connected to the formation of these groups, particularly focusing on those that influenced the earliest and most resilient local response to the pandemic. The presence of radical environmentalist activists is a better predictor of resilient community responsiveness than either the activity of the local state or the activity of more moderate community-based environmental civil society organizations. Conclusions are presented on the implications of these findings for the future of localism, social quality, and public policy in the United Kingdom.